The Development of Sequential Image Media in Learning to Write Expository Texts in Vocational School Semarang City - Rio Tri Astuti; Sri Suciati; Harjito Harjito (Jurnal Pendidikan Terapan, 2026)
Purpose: Writing ability is one of the basic language skills, by writing, students will apply speaking and writing skills. The purpose of this study is to determine the development, validity, effectiveness and practicality of developing sequential image media in learning to write expository texts for students. Method: The type of research used is Research and Development (R&D) development research. This research approach uses quantitative and qualitative approaches. The place of this research was conducted at Semarang City Vocational High School in class X. The development of sequential image media in learning to write expository texts for students has the following procedures: initial needs analysis, preparation of sequential image learning media drafts, expert and practitioner validation tests, revision of sequential image learning media drafts, limited trials, product revisions and preparation of reports. Findings: 1) The development of sequential image media is very necessary in learning to write expository texts because it can answer the needs of teachers and students. 2) The development of sequential image learning media through the drafting stage, the results of expert validation of 77% and practitioner validation of 78% are all included in the feasible category. Then the results of limited trials, the teacher response reached 90%, while the student response was at 91.5%, both included in the very practical category. The development of sequential image learning media can improve the quality of learning to write expository texts. Research Implications: This study implies that the use of sequential image media can enhance the effectiveness of expository text writing instruction and contribute to improving learning quality in vocational high schools. Originality: This study is original in developing sequential image media that is valid, practical, and effective for supporting expository text writing instruction and improving learning quality.